Corporate characteristics and ESG Disclosures in Malaysian Public-Listed Companies / Ho Wai Kee … [et al.] - Kee, Ho Wai; Mohd Sidik, Vivi Norazlina; Seng, Ng Foo; K. Suppiah, Susela Devi (Faculty of Accountancy, 2019)
Companies are changing the way business are conducted in the 21st Century aimed at contributing to the betterment of society holistically. The practice of disclosing company information relating to sustainability has increased intensely to response to the increased in demand for sustainability data from stakeholders. Corporate characteristics may influence the degree of disclosure of company information relating to sustainability. This study extends the literature on corporate characteristics and disclosure of sustainability practices by examining the influence of corporate characteristic on the disclosure of sustainability practices. The sampling frame is Malaysian public-listed companies, over the years 2014 to 2018, consisting of 285 observations. The study applies two stage least square regression analysis to validate the hypotheses and models. Using earnings per shares, return on equity, size of the company and market capitalization as the proxies of corporate characteristics and the Combined ESG Score as the proxy for the level of disclosure of sustainability practices, the findings show that return on equity and market capitalisation are significantly related to the level of disclosure of sustainability practices. The results show that return on equity and market capitalisation have an impact on the entity’s level of disclosure of sustainability practices. The practical implication of this research is that a well perform corporate with large market capitalisation is actively practice sustainability rather than to comply with regulatory requirements. Profitable companies with large market capitalisation willing to invest substantial amount in implementing sustainable practices to achieve lower operating costs and higher yield in long term. This study provides insightful input into the role of corporate characteristics to verify the company’s efficacy to produce a sustainability reporting which enable the stakeholders to know the company’s actual value.